SISTEM PENUNJANG KEPUTUSAN PEMILIHAN LAPANGAN PADA STARTUP AYOSPORTS MENGGUNAKAN METODE AHP - Ronald Kwandy; Syaiful Rahman; Izmy Alwiah Musdar (KHARISMA Tech, 2021)
This study aims to add a new type of sorting to the Ayosports startup where this new sort combines several types of sorting owned by competitors by building a decision support system in choosing sports fields. The decision support system is made using the Analytical Hierarchy Process (AHP) method using four criteria, namely rental prices, facilities, services, and types of fields. The alternatives used are three sports fields for each Ayosports category, namely basketball, badminton and futsal, so there are nine fields in total. The calculation results from the system that has been built show the same results as manual calculations using Ms. Excel. Then this system will be implemented on Ayosports when users search for empty fields and immediately sort them